Noninvasive assessment of short-term effects of cilazapril on cardiac and peripheral hemodynamics in essentially hypertensive patients - Donder, E.; Ayhan, O.; Colak, R.; Elmaci, H.; Isik, A.; Yildiz, C.; Luleci, C. (My University, 1993)
The effects of angiotensin converting enzyme inhibitor Cilazapril (2.5 or 5 mg daily) on cardiac and peripheral hemodynamics during short-term were investigated in 14 patients who were mild to moderately hypertensive. B-mode, M-mode, and continuous Doppler echocardiograms were performed before and 3 months after therapy by standard techniques. Also, values of heart rates, systolic, diastolic, and average blood pressures (SBP, DBP, ABP, mmHg), total peripheral vascular resistance (TPVR, mmHg/L/min), large artery distensibility (BAD, mmHg/ml), stroke volume, cardiac output, and ejection fraction were compared. Parameters about total mitral flow, early diastolic flow, late diastolic flow, aortic flow and also parameters of left atrial systolic time intervals (LASTI) and left ventricular systolic time ntervals (LVSTI) were evaluated. 3 months after Cilazapril therapy, no significant changes occurred in systolic and diastolic cardiac functions and heart rate, but TPVR (p < 0.01) and BAD (p < 0.05) decreased. Thus, significant decrease was observed in systolic (p < 0.0005), diastolic (p < 0.0005), and average BP (p < 0.0005).
Keywords: cilazapril; adult; aged; article; clinical article; diastolic blood pressure; electrocardiogram; essential hypertension; hemodynamics; human; systolic blood pressure